PERAN PESANTREN DALAM MENANGGULANGI DAMPAK NEGATIF GLOBALISASI - Fernanda, Moch Alvinas Naufal Fernanda Adie; Muhammad Husni (Najah Bestari, 2026)
Globalization brings progress in many aspects of human life, but it also brings negative effects, particularly regarding the moral values, culture, and behavior of the younger generation. Islamic boarding schools, as Islamic educational institutions that are both traditional and modern, play a crucial role in distilling values through religious education, moral development, and character building. This article examines how Islamic boarding schools contribute to addressing the negative effects of globalization through educational approaches, internalizing values, and enhancing social roles. The method used is desk research, exploring relevant literature on Islamic boarding schools, globalization, and values education. The findings of this study indicate that Islamic boarding schools can serve as a moral bulwark in society by emphasizing character education, strengthening religious culture, increasing digital literacy, and revitalizing social roles.